Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor

Liquefied petroleum gas sensing performance of cerium doped copper ferrite - Khandekar, M. S.; Tarwal, N. L.; Patil, J. Y.; Shaikh, F. I.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2013)
Undoped and cerium (Ce) doped nanocrystalline copper ferrite (CuFe2O4) materials were synthesized via the molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CuFe2O4 ferrite have been investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CuFe2O4. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Moreover, the gas sensing properties of sintered samples were studied towards different reducing gases such as liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sample with 4% cerium doped CuFe2O4 (Ce4) showed the maximum gas sensitivity (86%) towards LPG with fast response time of 5 s and good recovery time of 68 s. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrite; Gas sensor; Molten-salt method; TEM

La-Fe-O perovskite based gas sensors: recent advances and future challenges - Patil, Suraj S.; Babar, Bapuso M.; Nadargi, Digambar Y.; Shaikh, Faiyyaj I.; Nadargi, Jyoti D.; Sankapal, Babasaheb R.; Mulla, Imtiaz S.; Tamboli, Mohaseen S.; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (ACS OMEGA, 2024)
Keywords: ASSISTED SYNTHESIS; ETHANOL SENSING CHARACTERISTICS; LAFEO3 NANOPARTICLES